Pulmonary hypertension in congenital heart disease. (July 2018) - Pascall, Emma; Tulloh, Robert MR
Pulmonary hypertension is defined as a mean pulmonary arterial pressure ≥25 mmHg. We focus on its relevance in congenital heart disease, reviewing pathophysiology, diagnosis and management. Pulmonary hypertension is a relatively common complication of congenital heart disease, with adult prevalence between 5 and 10%. A multifactorial cause is recognized, relating to the size and nature of cardiac defect as well as environmental and genetic factors. More complex disease is increasingly recognized rather than pure Eisenmenger complex. Remodeling of the pulmonary vascular bed causes increased pulmonary vascular resistance diagnosed by a collection of investigations including echocardiography, exercise testing, cardiac catheterization, MRI and CT scanning. Management employs disease-modifying medications which are now used with increasing benefit.